HP : imprinting the global health sector - Jones, Jamie (SAGE knowledge. Cases., 2016)
Hewlett-Packard (HP) had a long history of engaging in corporate citizenship, dating back to its founding. By 2009, however, under the leadership of CEO Mark Hurd, the company had lost its focus on corporate social responsibility (CSR). The HP board, however, did not want to let CSR go by the wayside; in fact, it wanted HP to reorganize and restrategize its approach to corporate citizenship. This case focuses on this strategic transformation from traditional, cost-centre CSR to business-aligned social innovation.